Growth, Yield, and Water Productivity of Potato Genotypes Under Supplemental and Non-Supplemental Irrigation in Semi-Arid Areas of Northern Ethiopia - Niguse Abebe Misgina; Hussien Mohammed Beshir; Derbew Belew Yohannes; Gebre Hadgu Gebreyohanes (Agronomy)
Potato is the dominant tuber and root crop grown in Tigray. However, the productivity is very low due to moisture stress, traditional production techniques, and low-yielding varieties. Hence, this study aimed to optimize potato yield by selecting suitable genotypes under both supplemental and non-supplemental irrigation conditions. The study involved five potato genotypes and two irrigation levels used as treatments arranged in a split plot using a randomized complete block design with three replications. Results revealed a significant difference in days to flowering and maturity, marketable and total tuber yield, and water productivity due to the main and interaction effect of genotype and irrigation. CIP-3960478.90 recorded significantly higher marketable yield (27.13 t ha−1), total tuber yield (28.71 t ha−1), and water productivity (7.59 kg m−3) under supplemental irrigation. Genotype CIP-394611.112 had achieved high marketable yield (24.45 t/ha), total yield (25.60 t/ha) and total water productivity (8.51 kg m−3) under non-irrigated treatment. Additionally, the potato water requirements in September and October exceeded the rainfall amounts, suggesting that supplemental irrigation is necessary during this period for optimal yields. Likewise, genotypes CIP-394611.112 and CIP-3960478.90, are recommended for semi-arid areas to enhance tuber yield with or without irrigation.